Alternative strategy for management of ecotourism in Bunaken Island, Bunaken National Park, North Sulawesi, Indonesia - Rompas, Margresye D.; Kusen, Janny D.; Lasut, Markus T. (Universitas Sam Ratulangi, 2015)
Title (Bahasa Indonesia): Strategi alternatif untuk pengelolaan wisata bahari di Pulau Bunaken, Taman Nasional Bunaken, Sulawesi Utara, Indonesia The coral reefs of Bunaken Island is one of the attractions of the dive tourism, which has a diversity of marine life and the uniqueness of the objects for divers. To maintain its sustainability, it is necessary to study alternative management strategies of the reefs. This study aimed to describe and evaluate the current conditions in the management of marine tourism in Bunaken Island through formal and informal institutional analysis, and formulate alternative strategies as one of the priority strategies in the management of marine tourism of Bunaken Island. Alternative management strategies were analyzed using SWOT, while collecting data was carried out through field surveys using a questionnaire for visitors, communities, and stakeholder or industry-related tourism. Results of the study recommended that an alternative strategy for the management of Bunaken Island attractions should include: 1) increasing the active participation and involvement of local communities in the management of marine tourism destinations; 2) address the problem of garbage and cleanliness of the area; and 3) optimize the promotion of Bunaken Island adequately as the best maritime destination in the world. Terumbu karang di Pulau Bunaken merupakan salah satu objek wisata selam yang terkenal, di mana memiliki keanekaragaman biota laut dan keunikan panorama obyek penyelamannya. Untuk menjaga kelestariannya, maka perlu dikaji alternatif strategi pengelolaannya agar keberadaannya sebagai salah satu destinasi wisata yang penting bisa berkelanjutan. Penelitian ini bertujuan untuk mendeskripsikan dan mengevaluasi kondisi terkini dalam pengelolaan wisata baharÃ di Pulau Bunaken secara formal dan nonformal institusional; dan menyusun alternatif strategi sebagai salah satu prioritas strategi pengelolaan wisata baharÃ di Pulau Bunaken. Alternatif strategi pengelolaan dianalisis menggunakan SWOT, sedangkan pengambilan data melalui survei lapangan dengan menggunakan kuesioner pada pengunjung, masyarakat, dan stakeholder atau industri pariwisata terkait. Hasil penelitian merekomendasikan bahwa alternatif kebijakan untuk pengelolaan objek wisata di Pulau Bunaken meliputi: 1) meningkatkan peran aktif dan pelibatan masyarakat setempat dalam pengelolaan destinasi wisata bahari; 2) mengatasi masalah sampah dan kebersihan kawasan; dan 3) mengoptimalkan kembali promosi Pulau Bunaken secara memadai sebagai destinasi wisata bahari terbaik di dunia.